Analysis of the bacterial flora of periodontal pockets and evaluation of the diagnostic value and the validity of using the PET test in the detection of Sockransky’s red complex pathogens at various stages and degrees of periodontitis: Discussion of selected clinical cases - Adamus, Aleksandra; Cabon, Julia; Mrożek, Martyna; Rudzińska, Iwona; Sekuła, Sylwia; Wilk, Anna; Wierucka-Młynarczyk, Beata (Journal of Education, Health and Sport, 2022)
Introduction: In microbiological diagnostics, a significant role is played by the PET test based on a polymerase chain reaction developed thanks to medical engineering methods, which, by amplifying specific fragments of genetic material, enables the identification of microorganisms. As a consequence, it is possible to quantify and qualify a sample of biological material under study, which has found application in the diagnosis and treatment of periodontitis. Aim: The following paper shows the validity of carrying out the PET test in people with clinically diagnosed chronic periodontitis who also suffer from other loads, such as smoking or systemic diseases, as well as the physiological state of pregnancy. Another goal is also to confirm the presence of Sockransky’s red complex bacteria responsible for the development of periodontitis. Material and Methods: The research was carried out at the Clinic of Conservative Dentistry and Periodontal Diseases, performing an examination of 4 patients, and then after determining the deepest periodontal pockets, biological material was collected from them and sent to a bacteriological laboratory, where it was analyzed. Results: The quantitative and qualitative determination of the samples of biological material collected from the pockets of the patients showed the presence of the red complex bacteria according to Sockransky, especially the species: Treponema denticola and Porphyromonas gingivalis. Conclusions: In the studied clinical cases, the PET test confirmed the presence of bacteria responsible for periodontitis. The legitimacy of its use was also confirmed, emphasizing that it is a tool that can be used by a dentist in implementing therapeutic decisions in the treatment of periodontitis.